Exploring Different Parameters to Assess Left Ventricle Global and Regional Functional Analysis from Coronary CT Angiography - Silva, Samuel; Santos, Beatriz Sousa; Madeira, Joaquim (Computer graphics forum, 2012)
Coronary CT angiography is widely used in clinical practice for the assessment of coronary artery disease. Several studies have shown that the same exam can also be used to assess left ventricle (LV) function. Even though coronary CT angiography provides data concerning multiple cardiac phases, along the cardiac cycle, LV function is usually evaluated using just the end‐systolic and end‐diastolic phases. This unused wealth of data, mostly due to its complexity and the lack of proper tools, has still to be explored to assess if further insight is possible regarding regional LV functional analysis. Furthermore, different parameters can be computed to characterize LV function and though some are well known by clinicians others still need to be tested concerning their value in clinical scenarios. Based on these premises, we present several parameters characterizing global and regional LV function, computed for several cardiac phases over one cardiac cycle. The data provided by the computed parameters is shown using a set of visualizations allowing synchronized visual exploration of the different data. The main purpose is to provide means for clinicians to explore the data and gather insight over their meaning and their correlation with each other and with diagnosis outcomes.